(untitled) (Tempo e Argumento, 2022)
This article investigates candy and sweet consumption practices among children, products that in the first decades of the 20th century in Argentina became specific for childhood and one of its constitutive features, along with toys and games. The meanings of these practices are explored, linked to child desire and happiness, and their forms of social circulation, which played a role in the building of sociabilities, but also in the diffusion of social hierarchies and class, gender, age, and ethnic-racial distinction marks that profoundly cut through childhoods. The hypothesis guiding this study is that consumption ‒ a social practice that occurs within the framework of power relations, linked to the conformation of lifestyles and the making of social identities ‒ was one of the major arenas in which a ‘universal’ idea of childhood was delimited in the 1920s and 30s that had among its components a parental expectation and obligation to provide boys and girls with happiness. However, unequal access to consumption for children from different social classes contrasted sharply with this pretense of universality, helping to delineate class contours, lines, and boundaries that cut through childhoods in Argentina in the first half of the 20th century. This research is based on regular mass circulation press, such as the illustrated magazine Caras y Caretas, and on the working-class and left-wing press.